Rituximab in the treatment of systemic sclerosis. Literature review - L. A. Garzanova (Научно-практическая ревматология, 2023)
Systemic sclerosis (SSc) is one of the most severe systemic rheumatic diseases, characterized by the development of progressive skin fibrosis and damage to internal organs, accompanied by a decrease in the quality of life and high mortality. The treatment of SSc remains a difficult clinical task due to the complex pathogenesis. Nowadays therapy is complex and based on the dominant clinical and pathogenetic phenotype of SSc. However, standard therapy have limited potential to radically improve the prognosis of SSc, and often their use can lead to the development of intolerance and adverse events. In this connection, it remains relevant to study and introduce new approaches for the treatment of SSc, one of which is anti-B-cell therapy. Based on the data on the key role of B cells in the regulation of inflammatory and fibrotic processes in SSc, rituximab (chimeric monoclonal antibody to B-lymphocyte surface receptors – CD20) is increasingly being studied and used in clinical practice for the treatment of this disease. This review collects and analyzes data on the efficacy, safety and impact of rituximab on various manifestations of SSc.